High bioavailability of soil-derived dissolved organic carbon in the high Arctic fjord (Kongsfjorden, Svalbard Archipelago) - Koziorowska, Katarzyna; Makuch, Przemysław; Aguado Gonzalo, Fernando; Kuliński, Karol (Frontiers in Earth Science, 2025)
To assess the bioavailability in the soil-derived dissolved organic carbon (DOC), and to estimate potential remineralization kinetics for different bioavailable fractions of DOC, the long-lasting (180 days) incubation experiments of soil leachates were performed. The soil material was collected from the catchments of two contrasting rivers - Bayelva and Londonelva in Kongsfjorden (Arctic fjord in West Spitsbergen, Svalbard Archipelago). Both sampling sites were located close to the shore, where coastal erosion and tides directly affect the surface soil layer. The results indicate that the soil leachates contain a lot of DOC, which is highly bioavailable, even 68%–87% can be susceptible to biodegradation. The obtained decay curves allowed us to distinguish three DOC fractions: labile, semi-labile, and refractory. The contribution of the most labile DOC fraction is small and ranges from 13% in the Bayelva region to 25% in the Londonelva catchment but it remineralizes quickly once transported to the fjord, while the semi-labile DOC, whose half-life is measured in months, is much more abundant (74% and 43% of total DOC, respectively). These differences in the contribution of particular DOC fractions between stations can result from the different composition and provenance of organic matter. Nevertheless, this high lability of terrestrial DOC indicates that its supply to the fjords water column has the potential to play an essential role in sustaining the bacterial loop in the fjord and, through CO2 release, in amplifying ocean acidification in the coastal zone.